Pengenalan dan Simulasi Pertolongan Pada Korban Tersedak Dengan Metode Five To Five Pada Siswa Smk Palapa Pare Kediri - Vela Purnamasari; Nove Lestari; Neny Triana; Widyasih Sunaringtyas (WASATHON Jurnal Pengabdian Masyarakat, 2023)
Choking is a complete or partial blockage of the airways due to an object from outside the body, which can result in death if not treated quickly and appropriately. Choking incidents can occur anywhere, including in the school environment. When someone chokes, within a few minutes the individual will suffer from a general or complete lack of oxygen. The aim of this service activity is to provide introduction and education to class XII students about helping choking victims using the five to five method through a simulation strategy. The method of implementing this activity was carried out through counseling and simulation involving 25 class XII students at Palapa Pare Kediri Vocational School. The service activities were carried out in 3 sessions, namely: introduction to choking incidents through counseling, introduction to helping choking victims using the five to five method and simulation of how to help choking victims using the five to five method. The result of the service activity was an increase in students' knowledge and ability in helping choking victims using the five to five method, namely from some (50%) in the poor category (before the activity) to almost all (90%) in the good category. Education using a simulation approach can increase students' understanding of how to help choking victims with quick and precise implementation. Educational methods using a simulation approach can be used as a medium for conveying information to help when a victim is choking.